Coupling components and services for integrated environmental modelling. (August 2019) - Gao, Fan; Yue, Peng; Zhang, Chenxiao; Wang, Mi
Abstract: Integrated environmental modelling (IEM) couples environmental models, geoprocessing algorithms, and data together to solve complex environmental problems. There are two prominent modelling frameworks for IEM: component-based and service-oriented frameworks. The former one has been widely employed in local computer environments, and has its advantage in having concrete and community-wide tools. The latter one can take advantage of Web technologies for integrating distributed environmental models. However, the complex interaction between environmental models such as time marching models is still a challenge for integrating models on the Web. This paper suggests to take the best of both frameworks. Models are shared on the Web as WebSocket services. A hybrid approach to leverage OpenMI and WebSocket for coupling components and services is proposed to provide a flexible IEM environment. The result illustrates the applicability of the approach and demonstrates the advantage of WebSocket over the traditional HTTP approach in model execution. Highlights: A hybrid approach to couple OpenMI and WebSocket is proposed for an open standard based integrated environmental modelling. It supports complex model interaction on the Web. A comparative evaluation of model services between HTTP and WebSocket is presented.